Time study to improve productivity in a footwear production company, Lima, 2023 - Allauca Gamarra , Luis Enrique (2024)
For companies in the world, it is important to be more productive through techniques such as time study, in this sense, the study will provide evidence that explains how a company can be more productive with the standardization of the time required to execute its process. of production. The study was carried out with the objective of determining how time study improves productivity in a footwear production company, Lima, 2023, where an applied methodology was used, a quantitative approach at an explanatory level with a pre-experimental experimental design, with Regarding data collection, direct observation and documentary analysis were used. Likewise, the instruments used were a recording sheet, data sheet, stopwatch and measuring tape. The population was made up of the daily production of scissor-type sandals and the sample was the one mentioned for the period of one month, after the analysis the normal and standard time decreased by 9.75% and 8.92% respectively, productivity improved by 18.42% therefore both effectiveness and efficiency also at 4.12% and 13.06% respectively, thus concluding that the time study improved productivity in the footwear production company.